Integrating Strategic Management and Accounting Practices: A Pathway to Organizational Agility - Putri, Walla Astianty; Novitri, Bella Suci (Prodi Bisnis Digital Universitas Pahlawan Tuanku Tambusai, 2025)
In an era of rapid and dynamic business change, the need for organizational agility has become increasingly important. This research aims to analyze how integration between strategic management and accounting practices can form an effective path to improving organizational agility. Using a qualitative approach through case studies on several organizations in the industrial and service sectors, this study found that aligning strategic objectives with an adaptive accounting information system is able to accelerate decision-making, improve response to market changes, and strengthen internal innovation. Integrative practices such as strategy-based budgeting, Balanced Scorecard-based performance measurement, and value-based management accounting have been proven to play an important role in supporting organizational flexibility and adaptability. The results of this study provide theoretical contributions in the development of management and accounting integration models as well as practical recommendations for organizations that want to improve their competitiveness through the strengthening of internal structures and processes in an agile manner.